2010
DOI: 10.3748/wjg.v16.i32.4089
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of MUC2 and MUC5AC in progression of colorectal carcinoma

Abstract: Alterations in MUC expression occur during colorectal tumorigenesis. The transformation process in MC and SRCC may be different from that in the traditional adenoma-carcinoma sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 29 publications
5
57
1
Order By: Relevance
“…The older patients with carcinoma showed MUC-5AC overexpression, in comparison to the young (p<0.05). MUC-5AC expression was negatively associated with the depth of invasion, venous invasion, gastric NNM than gastric cancer in agreement with the data in ovarian carcinogenesis (Feng et al, 2002), indicating that down-regulated MUC-2 might play an important role in gastric carcinogenesis in agreement with another study (Bu et al, 2010). Additionally, MUC-2 expression was negatively correlated with tumor size, depth of invasion, and TNM staging of gastric cancer, in line with the previous reports (Rakha et al, 2005;İlhan et al, 2010), suggesting that reduced MUC-2 expression might be closely linked to the growth, invasion and progression of gastric cancer.…”
Section: Discussionsupporting
confidence: 81%
“…The older patients with carcinoma showed MUC-5AC overexpression, in comparison to the young (p<0.05). MUC-5AC expression was negatively associated with the depth of invasion, venous invasion, gastric NNM than gastric cancer in agreement with the data in ovarian carcinogenesis (Feng et al, 2002), indicating that down-regulated MUC-2 might play an important role in gastric carcinogenesis in agreement with another study (Bu et al, 2010). Additionally, MUC-2 expression was negatively correlated with tumor size, depth of invasion, and TNM staging of gastric cancer, in line with the previous reports (Rakha et al, 2005;İlhan et al, 2010), suggesting that reduced MUC-2 expression might be closely linked to the growth, invasion and progression of gastric cancer.…”
Section: Discussionsupporting
confidence: 81%
“…Similar observations regarding BRAF V600E in signet ring cell carcinoma have been noted by Ogino et al 35 Expression of the gastric mucin MUC5AC, a typical feature of serrated polyps, is also more common in mucinous and signet ring cell carcinomas, but is relatively uncommon in conventional adenocarcinoma. [47][48][49] These findings suggest that a subset of signet ring cell carcinoma may be related to the serrated pathway of carcinogenesis.…”
Section: Discussionmentioning
confidence: 86%
“…19,20,40 Various immunohistochemical studies have reported MUC2 positivity in colorectal cancers ranging from 21 to 63%. 19,39,[41][42][43] MUC5AC expression has been reported in 13-64% carcinomas, 16,42,44,45 with highest levels of expression in microsatellite-unstable/mismatch repair-deficient tumors 18,19,46 and those showing characteristic mucinous phenotype. 19,47 MUC5B and MUC6 expression in the lower gastrointestinal tract has remained relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%